The Effect of Physical Exercises According to Deny Foot to Improve Some Skillful and Muscular Abilities among Fencing Young Players - Muna Ihsan Muhammad Baqr1, Ali Naeem Ajeel2, Anmar Atshan Khargan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The research problem is about the lack of previous studies concerning with deny foot for feet through using the modern technological devices that record and save the quantities of the feet strength, by using Bluetooth. The researchers noted weakness in some muscle abilities, and reduce the level of physical performance for fencing players. This study aims at preparing exercises according to Deny Foot, which was put in the feet of the players, in order to improve some skillful and muscular abilities among fencing young players as well as to recognize the effect of these exercises on improving some skillful and muscular abilities among fencing young players. The researchers used the experimental method with the experimental design of two research groups (Equivalence), first experimental group and second experimental group. The research community of fencing competition has identified by choosing (10) players of Al-Jaish Sports Club for young people under the age of 17-18 years. The special exercises were applied for eight weeks and by three exercises units per week, the researchers used the Statistical Package for the Social Sciences (SPSS). The most important conclusions which the researchers reached that physical exercise have positively influenced on the development of some muscular abilities and skills for young fencing players. The researchers recommend the importance of investing modern devices and players in scientific colleges or specialized institutes and use them to provide a clear vision and information about the place and timelines.